Field Activity Management Learning Cycle 5-E Model in Linow Lake - Mardiana Silangen, Patricia (International Journal of Engineering and Technology, 2018)
Linow Lake is located in Tomohon City, North Sulawesi Province is an interesting geothermal area with a rich ecosystem of Physics study objects. Linow Lake has been utilized as an object of physics and physics education study of Physics Department Faculty Of Mathematics And Natural Sciences Manado State University, but there is no systematic design and has not been done regularly as part of the lecture. This research gradually designs and implements the management of field activities of learning cycleÂ  5-e model in integrated Linow lake with lectures. Research method using research and development design. The stages of materials and field activities developed adopt the 5E learning cycle (E1: engagement, E4: elaboration, E5: evaluation) as a benchmark for competence development, associated with the field activities stage (K1: introduction and attraction of the object study, K2: exploration of study objects and building skills: practicum, K3: deepening and elaborating knowledge and skills through independent research (or collaboration), and K4: comparative research, applied and competency evaluation for independent activity development The results show that management activities the field of learning cycle 5-e model can support the physics lecturing process that gives systemic direction to the students to carry out field activities and development of independent activities so as to build the comprehensive graduate student competence.Â Â